Assessing Heavy Metals in the Sele River Estuary: An Overview of Pollution Indices in Southern Italy - Fabiana Di Duca; Paolo Montuori; Elvira De Rosa; Bruna De Simone; Immacolata Russo; Raffaele Nubi; Maria Triassi (Toxics, 2024)
Rapid industrialization, coupled with a historical lack of understanding in toxicology, has led in an increase in estuary pollution, frequently resulting in unexpected environmental situations. Therefore, the occurrence of heavy metals (HMs) constitutes a major environmental issue, posing a serious risk both to aquatic ecosystems and public health. This study aimed to evaluate the levels of eight HMs (As, Hg, Cd, Cr, Cu, Ni, Pb, and Zn) in water, suspended particles, and sediment near the Sele River estuary (Italy) in order to assess their environmental impacts on the sea and health risks for humans. The results revealed an increasing order of HM concentration according to the scheme suspended particulate matter (SPM) > sediment (SED) > dissolved phase (DP) and a moderate contamination status in sediment. The health risk assessment indicated that the non-carcinogenic risk was negligible. Carcinogenic risk, expressed as the incremental lifetime cancer risk (ILCR), was negligible for Cd and Ni and within tolerable limits for As, Pb, and Cr. The findings suggested that, even if there are currently no specific limits for chemical parameters in the transitional waters of Italy, monitoring systems should be implemented to determine pollution levels and implement effective steps to improve river water quality and reduce human health risks.